On preconditioned iterative methods for solving (A−λB)x=0 - Evans, D. J. (Computing, 1984)
In this paper a preconditioned iterative method suitable for the solution of the generalized eigenvalue problem is presented. The proposed method in which no change in the structure of the original matrices occurs is suitable for the determination of the extreme eigenvalues and their corresponding eigenvectors of large sparse matrices derived from finite element/difference discretization of partial differential equations. The new method when coupled with the conjugate gradient algorithm yields a powerful algorithm for this class of problems.